Hukum Hutang Piutang Sebagai Modal Nikah: Studi di Kelurahan Pota, Sambi Rampas, Nusa Tenggara Timur - Hafid, Abdul; Syufa’at, Syufa’at (Fakultas Syariah INSURI Ponorogo, 2023)
This research discusses the problem of the habitual practice of debt by some communities in Pota Village, Sambi Rampas, East Nusa Tenggara. The habit of going into debt for marriage capital has become a tradition to this day, the purpose of this tradition is to make it easier for the men who are getting married. The way to collect capital for marriage is done by holding an event where with the aim of inviting invited guests and you are required to bring money with a free nominal but the event party will record the name and nominal that is brought, the purpose of recording is because it has an obligation to return according to the nominal brought by the invited guests. The purpose of this study was to find out the habit of practicing debt as a marriage capital according to Islamic law and to find out the tendency of people to get used to debt and debt behavior in such a way that it causes addiction and becomes a tradition in the social life of the Pota Village community. This type of research is field research where the research is in the Pota Village. The method used in this study uses a qualitative descriptive analysis method. This study found findings indicating that the habit of people in debt has become a hereditary tradition and based on the results of interviews with four informants from local residents indicate that the habit of debt receivables being used as capital for marriage is other than the tradition in Pota Village but found changes in the method of repaying debts that have been recorded where there is an excess of repaying the debt depending on the times and the value of the currency. It turns out that in the concept of fiqh muamalah the way to pay off debts that exaggerate includes usury.